PENGARUH KONTEN INSTAGRAM @Ezraalfatah TERHADAP PEMENUHAN KEBUTUHAN INFORMASI MENGENAI PANDUAN SKRIPSI BAGI FOLLOWERS - Adli, Miftahul; ,, Suyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to determine the influence of @ezraalfatah’s Instagram content on fulfilling the information needs related to thesis guidance among its followers. The @ezraalfatah account is an educational platform that shares content about thesis preparation, including topic selection, methodology, and thesis defense strategies. The research is motivated by the high demand for information among final-year students and the growing use of social media as a source of academic information. The study uses the Uses and Gratifications theory as its theoretical framework. Data were collected through an online questionnaire distributed to 100 active followers of @ezraalfatah using accidental sampling. The independent variable in this study is the quality of Instagram content, measured through indicators such as clarity, concise, concrete, correct, coherent, complete, and courteous. The dependent variable is the fulfillment of information needs, measured using current need approach, everyday need approach, exhaustive need approach, and catching-up need approach. The results show a significant influence of @ezraalfatah’s Instagram content on the fulfillment of information needs, with an R value of 0.888 and an R square value of 0.786. This indicates that 78.6% of the variation in information needs fulfillment can be explained by content quality. The regression test produced a significance value of 0.000 (< 0.05), confirming a positive and significant effect. In conclusion, the Instagram account @ezraalfatah contributes substantially to meeting the thesis-related information needs of its followers.. Keywords: Instagram, Social Media Content, Information Needs